2003
DOI: 10.1002/yea.1025
|View full text |Cite
|
Sign up to set email alerts
|

MIG1‐dependent and MIG1‐independent regulation of GAL gene expression in Saccharomyces cerevisiae: role of Imp2p

Abstract: Imp2p (Yil154c) is a transcriptional activator involved in glucose derepression of the maltose, galactose and raffinose utilization pathways and in resistance to thermal, oxidative or osmotic stress. We analysed the role of Imp2 in the regulation of GAL genes. Imp2 was shown to have a positive effect on glucose derepression of Leloir pathway genes and their activator gene GAL4. The effect of Imp2 on galactose metabolism was shown to be partially dependent on Mig1p. The Mig1-independent role depends on Nrg1p. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…No such consensus could be identified in the promoter sequence of IMA3 and IMA4, which makes possible that not-identified consensus variants of Mig1p binding site allow glucose repression. Alternatively, a MIG1-independent glucose regulation may apply to these genes and explain their modest glucose repression, as was already described for the GAL and MAL systems (41,42). Finally, three of the genes (IMA2, IMA3, and IMA4) harbor an STRE motif for the binding of Msn2/Msn4 proteins (43) together with a TATA box at Ϫ125 before the start codon, whose physiological relevance is discussed below.…”
Section: The Expression Of the Imax Genes Is Regulated By Carbon Sourmentioning
confidence: 91%
“…No such consensus could be identified in the promoter sequence of IMA3 and IMA4, which makes possible that not-identified consensus variants of Mig1p binding site allow glucose repression. Alternatively, a MIG1-independent glucose regulation may apply to these genes and explain their modest glucose repression, as was already described for the GAL and MAL systems (41,42). Finally, three of the genes (IMA2, IMA3, and IMA4) harbor an STRE motif for the binding of Msn2/Msn4 proteins (43) together with a TATA box at Ϫ125 before the start codon, whose physiological relevance is discussed below.…”
Section: The Expression Of the Imax Genes Is Regulated By Carbon Sourmentioning
confidence: 91%
“…Gal6p exhibits sequence‐independent binding to nucleic acids and its cytosolic localization suggests a role in the regulation of GAL mRNA levels [105,106]. Imp2p is another new example of a transcriptional factor with a Mig1 and Nrg1p negative repressors‐dependent and Gal6p‐independent positive effect on glucose derepression of GAL genes [107,108].…”
Section: Switching On and Off The Regulonmentioning
confidence: 99%
“…It has been demonstrated that low glucose concentrations activate SNF1 kinase, which result in the phosphorylation of the transcriptional repressor Mig1, causing its translocation to the cytoplasm and derepression of target genes (Alberti et al, 2003). SNF1 can also directly affect the transcription machinery through the interaction with the Srb/mediator complex of RNA polymerase II and histone phosphorylation (Lo et al, 2001).…”
Section: Sugar Signaling Pathwaysmentioning
confidence: 99%